Simulator training in gastrointestinal endoscopy – From basic training to advanced endoscopic procedures. Issue 3 (June 2016) - van der Wiel, S.E.; Küttner Magalhães, R.; Rocha Gonçalves, Carla Rolanda; Dinis-Ribeiro, M.; Bruno, M.J.; Koch, A.D.
Abstract: Simulator-based gastrointestinal endoscopy training has gained acceptance over the last decades and has been extensively studied. Several types of simulators have been validated and it has been demonstrated that the use of simulators in the early training setting accelerates the learning curve in acquiring basic skills. Current GI endoscopy simulators lack the degree of realism that would be necessary to provide training to achieve full competency or to be applicable in certification. Virtual Reality and mechanical simulators are commonly used in basic flexible endoscopy training, whereas ex vivo and in vivo models are used in training the most advanced endoscopic procedures. Validated models for the training of more routine therapeutic interventions like polypectomy, EMR, stenting and haemostasis are lacking or scarce and developments in these areas should be encouraged.